Formação continuada de professores/as da educação infantil: um olhar atento sobre a realidade da rede municipal de ensino de Bagé/RS - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This work is the result of a qualitative research which discussed about the continuing education process for teachers working in early childhood education in the municipal teaching Bagé/RS, aiming to identify the way teachers build their knowledge in continuing education courses participating. He questioned yourself about the vacancies disparity offered for continuing education course offered to teachers of private schools and public schools? What are the contributions and lessons that continued teacher training enables teachers? And how teachers apply the learning in their workspaces? The interest in this topic stems from my work is teachers te of early childhood education in a private school and participating in a continuing education for teachers childhood education, offered by the Department of Bagé county of Education in the year 2014. The research It was of course in qualitative perspective covering the period being studied, between July of 2014 and other training offered in 2015. The subjects of research Children Education coordinator of the SMED and 6 teachers who work in a school of Education childhood county Bagé teaching. For data collection the following research instruments were used questionnaires and interviews. Data were analyzed by means of discursive text analysis which according to Moraes (2003), provides us with a look more detailed and dynamic, keeping in mind that the researcher in this regard, to do a description and interpretation in order to comply, in this case, the lines of the research subjects that have their peculiarities and similarities, and the authenticity of the documents examined. Through research composed a significant database, making a detailed and revealing study's findings, as the continuing training policies of early childhood education offered by SMED, as well as knowledge of the ways in which these professionals, educators, perform continuing education and use the learnings gained from this training for their teaching practices. The results were that teachers build their knowledge through the analysis of daily practices, arguing with his fellow teachers new opportunities to streamline your actions and students, whether everyday or different, using materials available in the formations participate, enabling teachers exchanges of theoretical and practical information, also telling their one experience to the other, causing what is discussed egalitarian way in most early childhood education schools, can come to terms and that new proposals arise and are applied successfully in schools.
Keywords: Educação; Formação continuada; Educação infantil; Formação docente; Education; Early childhood education; Continuing education; Public policy; CNPQ::CIENCIAS HUMANAS